Microscopic and elemental analysis of jaw bone tissue in injury - N. N. Kataeva; N. G. Sarkisyan; N. S. Chumakov; K. A. Khlystova; O. M. Medvedeva; A. S. Shmygalev (Медицинская иммунология, 2023)
Since the jawbone tissue is injured at the stage of metal dental implant introduction, the problem of inflammatory complication development leading to a breakdown in osseointegration remains relevant. Of interest are the immunological mechanisms of inflammatory process development during the emission of metal nanoparticles, as well as the mechanisms of its subsidence after the removal of a metal object. Microscopic and elemental analysis of the bone tissue of the Wistar rat lower jaw after artificial traumatization was carried out. During the experiment, the situation of presence of a metal foreign body in the bone bed was simulated. An insulin needle was injected into the connective tissue of the lower jaw, followed by its removal after seven days. Microscopic analysis of bone tissue was performed using a Tesscan Vega 4 scanning electron microscope. The teeth alveoli cortical layer surface, connection of the jaws with a gap, stratification of the cartilaginous layer were determined at low magnification in direct projection. Using higher magnification in the direct projection there are visible dense-structural crystalline inclusions, foci of necrosis in the area of junctions of the jaws alveolar processes. The elemental composition of bone tissue was obtained by atomic emission spectroscopy by iCAP 6300 Duo. In the test sample, the quantitative ratio of calcium and phosphorus was 1.68, which slightly exceeds the optimal value of 1.67. An upward change in this ratio indicates a decrease in phosphorus level, which can be interpreted as local osteoporosis. In addition, the following elements were found: Bi, Ga, Pb, Ti, Zn in the amount of 0.03-0.06 mass percent. The list of these elements corresponds to the chemical composition of an insulin needle, indicating the penetration of metal particles into bone bed tissues. The emission of nanoparticles and their subsequent association to micro- and submicron sizes, their persistence, as well as biocorrosion in areas of active bone formation can be a trigger for the development of an aseptic inflammatory process. This effect is due to both a direct damaging factor and an indirect effect through specific signal molecules produced in response to tissue damage.